Glucagon-like peptide-1 receptor agonists: a review from a cardiovascular perspective - Turkistani, Yosra (Frontiers in Cardiovascular Medicine, 2025)
IntroductionGlucagon-like peptide-1 receptor agonists (GLP-1 RA) are novel agents with proven cardiovascular (CV) benefits. GLP-1 RAs have been used for diabetes and found to improve CV outcomes in diabetic and nondiabetic patients. They are authorized for treating obesity. Our narrative review discussed the CV benefits of GLP-1 RAs in terms of controlling CV risk factors and improving CV outcomes in diabetic and nondiabetic patients regardless of their CV history, and the CV perspectives related to their use in clinical practice.Areas coveredLiterature was searched with no limits on date or language, using various combinations of keywords. Data on the CV benefits of GLP-1 RAs and their use in clinical practice were summarized.ResultsSeveral studies have discussed the CV beneficial effects of GLP-1 RAs in terms of reducing blood pressure, lipid levels, body weight, risk for arrhythmias, reducing the risk of major adverse CV events, and hospital admission for heart failure.ConclusionThe cardioprotective effects and low risk of hypoglycemia of GLP-1 RAs make them preferred agents in any multidisciplinary approach aiming to reduce CV disease burden and improve prognosis. Cardiologists are encouraged to strongly consider the CV benefits of GLP-1 RAs in their risk-reduction strategies.